A review of audio based steganography and digital watermarking - Mat Kiah, M.L.; Zaidan, B.B.; Zaidan, A.A.; Mohammed Ahmed, A.; Al-Bakri, S.H. (2011)
With the increasing usage of digital multimedia, the protection of intellectual property rights problem has become a very important issue. Everyday, thousands of multimedia files are being uploaded and downloaded. Therefore, multimedia copyrights become an important issue to protect the intellectual property for the authors of these files. In this paper, the domains of digital audio steganography, the properties of H.A.S, the audio and the digital representation transmission environments, and its software metric, are discussed. The main purpose of this paper is to provide a proper background on the usage of audio file for the purpose of implementing new approaches and techniques in digital watermarking and steganography. Â©2011 Academic Journals.